Explanatory Translation Beyond the Kuhnian Model of Conceptual Change - Rantala, V.; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2002)
In this book, Veikko Rantala makes a systematic attempt to understand cognitive characteristics of translation by bringing its logical, pragmatic and hermeneutic features together and examining a number of scientific, logical, and philosophical applications. The notion of translation investigated here is called explanatory, but it is not a translation in the standard sense of the word since it admits of conceptual change. Such translations can take various degrees of precision, and therefore they can occur in contexts of different kinds: from everyday discourse to literary texts to scientific change. The book generalizes some earlier approaches to translation, especially the one presented in David Pearce's monograph Roads to Commensurability. Rantala argues that the notion has something in common with Thomas Kuhn's earlier conception of scientific change and his views of language learning, but it can be used to go beyond Kuhn's well-known ideas and challenge his criticism concerning the import of the correspondence relation.
The Pragmatics and Hermeneutics of Conceptual Change -- Prologue: The Correspondence Principle -- Translation -- Examples and Applications of Local Translation -- Global Translation -- The Logic and Pragmatics of Scientific Change -- The Correspondence Relation -- Intertheoretic Explanation -- Case Studies -- The Formal Basis of the Correspondence Relation -- Theories and Logics -- A Formal Treatment of Case Studies.
Keywords: Philosophy and science; Language and languages$1 (BPhilosophy.s; Logic; Mathematical physics; Artificial intelligence; Philosophy of Science; Philosophy of Language; Logic; Theoretical, Mathematical and Computational Physics; Artificial Intelligence